2002
DOI: 10.2134/jeq2002.1657
|View full text |Cite
|
Sign up to set email alerts
|

Imazaquin Adsorbed on Pillared Clay and Crystal Violet–Montmorillonite Complexes for Reduced Leaching in Soil

Abstract: Ground water pollution due to herbicide leaching has become a serious environmental problem. Imazaquin [2-(4-isopropyl-4-methyl-5-oxo-2-imidazolin-2-yl)quinoline-3-carboxylic acid] is an herbicide used to control broadleaf weeds in legume crops. Imazaquin is negatively charged at the basic pH of calcareous soils and exhibits high leaching potential in soils. Our aim was to design formulation of imazaquin to reduce herbicide leaching. Imazaquin sorption on pillared clay (PC) and crystal violet (CV)-montmorillon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Herbicides are usually released into the environment through the industrial and agricultural operations resulting in them being detected in many surface and ground waters at extremely low concentrations. The removal of these compounds from water may be achieved with a variety of absorbents but the complete removal of these at low concentration is still somewhat difficult [1][2][3][4][5][6][7][8][9]. This study clearly illustrates that wide range of compounds with varied structures, sizes and functionality can be adsorbed effectively from aqueous systems only by the fine tuning of the adsorption sites [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 81%
“…Herbicides are usually released into the environment through the industrial and agricultural operations resulting in them being detected in many surface and ground waters at extremely low concentrations. The removal of these compounds from water may be achieved with a variety of absorbents but the complete removal of these at low concentration is still somewhat difficult [1][2][3][4][5][6][7][8][9]. This study clearly illustrates that wide range of compounds with varied structures, sizes and functionality can be adsorbed effectively from aqueous systems only by the fine tuning of the adsorption sites [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 81%
“…SWy-2 montmorillonite was obtained from the Source Clays Repository (Clay Minerals Society, Columbia, MO); the CEC of the clay is reported as 0.8 mol/kg [22]. 2,4,5-TCP (99%) and CV were purchased from Aldrich (Germany), whereas picric acid solution (1.2%) was obtained from Ridley (Reidelde Haan, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Interactions of the monovalent cationic dye crystal violet (CV) with montmorillonite were extensively studied and modeled [20], and the ability of the montmorillonite-CV complex to sorb anionic dyes and nonionic organic pollutants from water was investigated [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…For the specific case of imazaquin, several controlled release formulations based on clays and organoclays have been designed. Polubesova et al . showed that an organoclay‐imazaquin formulation prepared from a crystal violet‐montmorillonite complex reduced imazaquin leaching in soil.…”
Section: Introductionmentioning
confidence: 99%